The risk of acute liver injury associated with the use of antibiotics—evaluating robustness of results in the pharmacoepidemiological research on outcomes of therapeutics by a European consortium (PROTECT) project. (2nd August 2015) - Udo, Renate; Tcherny‐Lessenot, Stéphanie; Brauer, Ruth; Dolin, Paul; Irvine, David; Wang, Yunxun; Auclert, Laurent; Juhaeri, Juhaeri; Kurz, Xavier; Abenhaim, Lucien; Grimaldi, Lamiae; De Bruin, Marie L.
Abstract: Purpose: To examine the robustness of findings of case–control studies on the association between acute liver injury (ALI) and antibiotic use in the following different situations: (i) Replication of a protocol in different databases, with different data types, as well as replication in the same database, but performed by a different research team. (ii) Varying algorithms to identify cases, with and without manual case validation. (iii) Different exposure windows for time at risk. Methods: Five case–control studies in four different databases were performed with a common study protocol as starting point to harmonize study outcome definitions, exposure definitions and statistical analyses. Results: All five studies showed an increased risk of ALI associated with antibiotic use ranging from OR 2.6 (95% CI 1.3–5.4) to 7.7 (95% CI 2.0–29.3). Comparable trends could be observed in the five studies: (i) without manual validation the use of the narrowest definition for ALI showed higher risk estimates, (ii) narrow and broad algorithm definitions followed by manual validation of cases resulted in similar risk estimates, and (iii) the use of a larger window (30 days vs 14 days) to define time at risk led to a decrease in risk estimates. Conclusions: Reproduction of a study using a predefined protocol in different database settings is feasible, although assumptions had to be made and amendments in the protocol were inevitable. Despite differences, the strength of association was comparable between the studies. In addition, the impact of varying outcome definitions and time windows showed similar trends within the data sources. Copyright © 2015 John Wiley & Sons, Ltd.